Global scientific trends in hypercholesterolemia research from 2003 to 2023: a data-driven bibliometric and visual analysis - Guo, Haoxin; Wang, Qihui; Wang, Yinling; Dong, Xiaolong; Wang, Zhongqing; Kang, Hui; Cheng, Shitong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiovascular disease remains the leading cause of mortality and disability worldwide. Hypercholesterolemia is a significant causal factor of ischemic heart disease, contributing to half of all cardiovascular fatalities.MethodsThis study utilized bibliometric tools to offer a comprehensive overview of the current research trends in hypercholesterolemia. The full records and cited references from 18,641 publications (2003–2023) were retrieved from the Web of Science Core Collection, and bibliometric analysis was conducted using VOSviewer.ResultsThe United States and Harvard University had the most significant influence among the countries/regions and research institutions, respectively. Among the researchers, Kastelein J.J.P. published the highest number of related articles, whereas publications by Sabatine M.S. had the highest average citation. The top 10 keywords were atherosclerosis, familial hypercholesterolemia, cardiovascular disease, risk, risk factors, gene expression, coronary heart disease, low-density lipoprotein, statins, and prevalence. These high-frequency keywords were clustered into groups based on the pathogenic mechanisms, disease prevalence and prevention, drugs and treatments, and familial hypercholesterolemia. These clusters denote distinct study fields and current research hotspots for hypercholesterolemia.ConclusionThrough bibliometric and visual analysis, this study comprehensively assessed global research trends and focal areas within hypercholesterolemia, offering valuable insights into current and future research directions in the field. Further research is needed on the relationship between the intestinal microbiota and cholesterol metabolism and on the advancement of microbiota therapy and precision medicine.